2019
DOI: 10.1177/2050312119871066
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and attitude toward lumbar puncture among adults in Riyadh, Saudi Arabia: A cross-sectional study

Abstract: Objective: The aim of this study is to evaluate knowledge of and attitudes toward the lumbar puncture procedure among adults in Riyadh region, Saudi Arabia, 2018. Methods: This study used a quantitative cross-sectional evaluation of the responses of adults aged ⩾18 years from the Saudi Telecom Company database in the Riyadh region of Saudi Arabia to an online survey between October and December 2018. The questionnaire included questions on knowledge, attitudes, and demography. The questionnaire was pretested a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…A recent study found that a poor understanding of the LP was associated with negative attitudes about the procedure (21). Interventions designed specifically to demystify the LP and to address post procedure side-effects may normalize the procedure and improve enrollment rates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that a poor understanding of the LP was associated with negative attitudes about the procedure (21). Interventions designed specifically to demystify the LP and to address post procedure side-effects may normalize the procedure and improve enrollment rates.…”
Section: Discussionmentioning
confidence: 99%
“…12 There was also a significant correlation according to age, notably 46 years and over. 12 The attitudes toward LP were markedly negative among those who feared injections in the lumbar region. There is a lack of sufficient public knowledge of the LP technique, and the general public knowledge suggests that LP is unacceptable.…”
Section: Introductionmentioning
confidence: 89%
“…aimed to assess the awareness and attitudes of people in the area of Riyadh, Saudi Arabia regarding LP. 12 A significant combination between acceptable level of information and an acceptable level of attitude were found via a multivariate logistic regression. 12 There was also a significant correlation according to age, notably 46 years and over.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations